Organisational Trust in the Governance of Tourism Development - Yusdi Nurdin Lamatenggo; Jamaluddin Jompa; Akmal Ibrahim; Didik Iskandar (Journal La Sociale, 2026)
In a multi-stakeholder partnership, the success of governance is determined not only by the structure and the actors involved, but also by the level of trust between the organisations involved. However, in the practice of tourism development in West Papua Province, trust between actors has not yet been fully established. This study aims to analyse organisational trust within a multi-stakeholder partnership in the governance of tourism development in West Papua Province. The study employs a qualitative approach using a case study strategy. Data were collected through in-depth interviews, observation, and documentation, and were subsequently analysed using an interactive model through the stages of data reduction, data presentation, and drawing conclusions. The research findings indicate that organisational trust is influenced by three key aspects. Firstly, competence trust, which is not yet optimal, characterised by disparities in capacity and capability among the actors. Secondly, goodwill trust, which remains limited, evident in the lack of strong commitment, transparency and good faith in the collaboration. Third, behavioural trust is inconsistent, reflected in the weak implementation of agreements and a lack of accountability in programme delivery. These three dimensions are interrelated and influence the quality of relationships and the effectiveness of multi-stakeholder partnerships. Organisational trust within multi-stakeholder partnerships remains suboptimal and requires strengthening in terms of competence, commitment, and behavioural consistency among actors to enhance the effectiveness of tourism development governance.